Analisis Sistem Rekrutmen Dengan Mempertimbangkan Kinerja Karyawan Pada Perusahaan Outsourching PT. Nawa Setia Perkasa - Azizah, Miftakhul; Darul Fadli, Uus Mohammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
As competition gets tougher, the business world must acquire skilled personnel. Developing a recruitment strategy is an important first step in helping businesses attract top talent. The aim of this research is to ascertain how recruitment practices affect employee performance. PT employees. Nawa Setia Perkasa is the population used in this research, and respondents were chosen as supporting informants. Using survey data, a qualitative descriptive research approach was used. The conclusion of this study shows that a number of other variables, including previous work history, educational background, and personal traits, are also determining factors in the quality of an employee. Additionally, a number of circumstances can make recruiting efforts futile, such as: For example: Job postings are not detailed enough, and hiring practices are not in line with company policies.